Identification of the (183)RWTNNFREY(191) region as a critical segment of matrix metalloproteinase 1 for the expression of collagenolytic activity. - Chung, L; Shimokawa, K; Dinakarpandian, D; Grams, F; Fields, G; Nagase, H (2000)
Matrix metalloproteinase 1 (MMP-1) cleaves types I, II, and III collagen triple helices into (3/4) and (1/4) fragments. To understand the structural elements responsible for this activity, various lengths of MMP-1 segments have been introduced into MMP-3 (stromelysin 1) starting from the C-terminal end. MMP-3/MMP-1 chimeras and variants were overexpressed in Escherichia coli, folded from inclusion bodies, and isolated as zymogens. After activation, recombinant chimeras were tested for their ability to digest triple helical type I collagen at 25 degrees C. The results indicate that the nine residues (183)RWTNNFREY(191) located between the fifth beta-strand and the second alpha-helix in the catalytic domain of MMP-1 are critical for the expression of collagenolytic activity. Mutation of Tyr(191) of MMP-1 to Thr, the corresponding residue in MMP-3, reduced collagenolytic activity about 5-fold. Replacement of the nine residues with those of the MMP-3 sequence further decreased the activity 2-fold. Those variants exhibited significant changes in substrate specificity and activity against gelatin and synthetic substrates, further supporting the notion that this region plays a critical role in the expression of collagenolytic activity. However, introduction of this sequence into MMP-3 or a chimera consisting of the catalytic domain of MMP-3 with the hinge region and the C-terminal hemopexin domain of MMP-1 did not express any collagenolytic activity. It is therefore concluded that RWTNNFREY, together with the C-terminal hemopexin domain, is essential for collagenolytic activity but that additional structural elements in the catalytic domain are also required. These elements probably act in a concerted manner to cleave the collagen triple helix.